Variation in the helminth community structure in spiny mice (Acomys dimidiatus) from four montane wadis in the St Katherine region of the Sinai Peninsula in Egypt - Behnke, Jerzy M.; Harris, Philip D.; Bajer, Anna; Barnard, Christopher J.; Sherif, Nour E.; Cliffe, Laura; Hurst, Jane; Lamb, M.; Rhodes, Alex; James, Mike; Clifford, Simon; Gilbert, Francis; et al. (Cambridge University Press, 2004)
We compared helminth communities in spiny mice (Acomys dimidiatus) from 4 wadis in the arid montane region of the southern Sinai in Egypt, in a 4-week period in late summer. Total helminth species richness was 14 (8 nematodes, 5 cestodes and 1 acanthocephalan) with 94% of mice carrying at least 1 species and an overall mean species richness of 1.85. The most prevalent parasites were Protospirura muricola (47.8%) and Dentostomella kuntzi (46.3%). One larval cestode, Joyeuxiella rossicum, represents a new host record. The helminth community was dominated by intestinal nematodes (88.7%) of which 58.2% were arthropod-transmitted heteroxenic species. At the component community level, 70% of the worms were recovered from mice in just two wadis (Gharaba and Tlah) and 48.6% of intestinal nematodes were from Wadi Gharaba. Although only 7 species of helminths were recorded from Wadi Gharaba, this site gave the highest Berger-Parker dominance index because P. muricola. P. muricola was also dominant in Wadi El Arbaein whilst Syphacia minuta was the dominant species in Wadis Gebal and Tlah. At the infracommunity level, mean species richness and Brillouin’s index of diversity were highest in Wadi Tlah and lowest in Wadi Gebal, and the former was age dependent. Whilst mice from different wadis differed in the nematodes that were most common, those from Wadi Gharaba carried the highest mean number of worms/mouse. The abundance of P. muricola in particular varied markedly between sites: Wadi Gharaba was distinct as the site showing the highest mean worm burden whereas mice from Wadi Gebal were uninfected. None of the directly transmitted oxyuroid nematodes showed significant variation in abundance between wadis, or host sex or age classes. Overall, the single extrinsic factor in the study, site of capture, was more important than the intrinsic factors in explaining variation in helminth communities in the region. We conclude that in the high mountains of southern Sinai, each wadi is distinct in terms of its rodent parasites, and hence we expect spatially different coevolutionary pressures on their hosts, with resultant variation in life-histories.